Analysis of the Quality of Islamic Religious Education Test Items Based on the SOLO Taxonomy for Developing Summative Assessment in Schools - Nur Fadilah Ramadhany; Suwadi Suwadi; Amri Saputra (PT. Pusmedia Group Indonesia, 2026)
Islamic Religious Education (IRE) assessment is still frequently oriented toward the ability to recall information, recognize terms, understand definitions, and determine legal rulings textually. Consequently, IRE test items may measure only basic knowledge rather than depth of understanding, interconceptual relationships, legal reasoning, reflection, and the application of Islamic values in everyday life. This study examines the extent to which IRE test items represent the complexity of students’ understanding based on the SOLO Taxonomy framework. Employing a descriptive qualitative approach and content analysis, the study treats IRE test items as assessment texts that represent the cognitive demands placed on students. The data comprised 50 senior high school IRE test items obtained from a school in Batam City. The data were analyzed using Krippendorff’s content analysis framework through a critical reading of each item, identification of the structure of its cognitive demands, classification according to SOLO Taxonomy levels, tabulation of frequencies and percentages, and interpretation of assessment-quality patterns. The results show that, of the 50 items analyzed, 35 items (70%) were unistructural, 5 items (10%) were multistructural, 9 items (18%) were relational, and 1 item (2%) was extended abstract, while no prestructural items were identified. These findings indicate that IRE test items remain dominated by basic cognitive demands and therefore do not yet fully represent assessment that promotes interconceptual connections, legal reasoning, reflection, and the application of Islamic values in real-life contexts. This study recommends restructuring the weighting and composition of IRE test items in assessment blueprints by increasing the proportion of relational and extended abstract items. This improvement can be achieved through case-based stimuli, reasoned questions, analyses of interconceptual relationships, attitudinal reflection, and the application of Islamic values to authentic situations, thereby aligning assessment more closely with learning outcomes and principles of meaningful assessment.